صورة قادة الكورد كما تعكسها النشرات الفضائية الكوردية دراسة تحليلية مقارنة بين قناتي)w da Ru وNRT) - م.م وريا روستم محمد - قسم االعالم كلية االداب /جامعة صالح الدين - اربيل, (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Kurdish private channels are seen as the most effective media tools, which participate in constructing media images on the Kurdish leaders and Kurdish people, this is due to massive viewers in the regions. It is also seen as a substitute to the political parties channels run by the parties that present a newer image and different from political parties media. This study aims to discover the role of the Kurdish satellite channels in constructing images to the Kurdish leaders through analyzing media images from what comes out from satellite channels on the Kurdish leaders, and comparing the images between (NRT and RUDAW). The study depends on a contextual analysis by using qualitative and quantitative content analysis on the comparing method in terms of similarities amongst the News explanation to the Kurdish questions that presented through (NRT and RUDAW). This study consists of five main parts: First, the framework of the study, Second, Theoretical framework, Third, field study framework and fourth, is about data analysis and recommendations to the study.